The Mughals and the Sufis - Alam, Muzaffar (Albany : State University of New York Press, 2021)
"Examines the relationship between Mughal political culture and the two dominant strains of Islam's Sufi traditions in South Asia: one centred around orthodoxy, the other focusing on a more accommodating and mystical spirituality"
Keywords: Sufism -- History -- India; Islam and politics -- India